2018
DOI: 10.22452/jati.vol23no1.3
|View full text |Cite
|
Sign up to set email alerts
|

Causality Between Female Fertility and Female Labour Force Participation in Asean-5

Abstract: Researches on whether female fertility determines labour force participation or vice versa have reached mixed results. A high participation of females in the labour market can limit the family size, and conversely, low female fertility can free up their time and increase their participation in the labour market. As such, this paper sets out to answer the question of "What causes what?" Having established the existence of cointegration for Malaysia, Singapore, Thailand, the Philippines and Indonesia (hereafter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Therefore, for sub-Saharan Africa's GDP to increase, female labour has to postpone child birth so that the women can be integrated into the various sectors like agriculture, industrial and service sectors so as to contribute to the overall GDP. The inverse relationship result of fertility rate is consistent with the work of Subramaniam et al (2015) and Mishra and Smyth (2010) who found an inverse relationship between fertility rate and female labour force participation.…”
Section: Hausman Test and Estimate Of Long-run And Short-run Relation...supporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, for sub-Saharan Africa's GDP to increase, female labour has to postpone child birth so that the women can be integrated into the various sectors like agriculture, industrial and service sectors so as to contribute to the overall GDP. The inverse relationship result of fertility rate is consistent with the work of Subramaniam et al (2015) and Mishra and Smyth (2010) who found an inverse relationship between fertility rate and female labour force participation.…”
Section: Hausman Test and Estimate Of Long-run And Short-run Relation...supporting
confidence: 89%
“…The empirical findings did not support the U-shaped hypothesis, rather revealed no significant relationship between economic growth and FLFPRs. Subramaniam et al (2015) and Mishra and Smyth (2010) in their study, observed an inverse connection between fertility rate and female workforce participation among 28 JBSED OECD and ASEAN countries. Idowu and Owoeye (2019) employ seemingly unrelated regression (SUREG) including control variables such as female education, fertility and manufacturing growth rate for geographically sub-grouped 20 African countries, and they suggest that there is an inverted U-shaped relationship.…”
Section: Empirical Review Of Flfprmentioning
confidence: 83%
“…In line with the literature on panel causality related to female work participation, such as Aljebrin (2012), Subramaniam et al (2018), Shittu and Abdullah (2019), and Idowu and Owoeye (2019), this study utilises popular long-run estimation measures, such as FMOLS, DOLS and PMG estimation approaches. Pedroni (2000) argues that if the time series of the panel observations are cointegrated, the panel OLS estimation may generate uncertain results.…”
Section: Long-run Estimatesmentioning
confidence: 99%